Uso de lipossomas microestruturados na formulação de vacinas de subunidade protéica HspX para tuberculose - Trentini, Monalisa Martins (2014)
Tuberculosis is a disease that affects thousands of people in the World. Although Brazil Health Program had achieved the goal of reducing to 50% the rate of death induced by Tuberculosis, this disease continues to be the second cause of death by infectious disease. One of the main problems to control the disease is the low efficacy of BCG vaccine in protecting young adults. The development of new vaccines that induces long lasting immune response or that stimulate the immunity induced by BCG may improve the control of TB spreading. This study evaluated the use of microstructured liposomes containing HspX with or without MPL or CpG DNA adjuvants as vaccine for tuberculosis. The HspX specific humoral and cellular immune responses were compared between the different vaccine formulations. All vaccines containing liposome microparticules and HspX were immunogenic and antigenic. Vaccines formulated with CpG DNA and HspX induced the strongest humoral and cellular immune responses, mainly by generating IFN- and TNF-by both CD4 and CD8 T cells. HspX and MPL mainly induced CD8 T cell activation and humoral specific responses. After protection efficacy evaluation against Mycobacterium tuberculosis challenge, the vaccine formulation that reduced both lung inflammatory lesions and the bacterial load was the microstructured liposome containing HspX and CPG DNA. These results show for the first time the use of microstructured liposome as adjuvant and delivery system in HspX vaccine formulation for tuberculosis.